Panus tigrinus as a potential biomass source for reactive blue decolorization: isotherm and kinetic study - Munjid Mustafaa, Monawar; Jamal, Parveen; Al-Khatib, Ma'an Fahmi Rashid; Mahmodb, Safa Senan; Jimat, Dzun Noraini; Ilyas, Nurul Najihah (Elsevier, 2017)
Background: Textile and dye industries pose a serious threat to the environment. Conventional methods used for dye treatment are generally not always effective and environmentally friendly. This drove attention of scores of researchers to investigate alternative methods for biodegradation of dyes using fungal strains. In this work, whiterot fungus (Panus tigrinus) was used as a biosorbent for the decolorization of Reactive Blue 19. The process parameters that were varied were: initial concentration (50-150 mg/L), time (30-90 min) and pH (2-6). Also, in order to gain important data for the evaluation of a sorption process, the equilibrium and the kinetics of the process were conducted. Results: White-rot fungus showed great potential in decolorizing Azo dyes. The strain showed the maximum decolorization of 83.18% at a pH of 2, 90 min and an initial concentration of 50 mg/L. The Langmuir isotherm described the uptake of the reactive blue 19 dye better than Freundlich isotherm. The kinetic data were analyzed and the result showed that the dye uptake process followed the pseudo second-order rate expression. Conclusion: The biosorption process provided vital information on the process parameters required to obtain the optimum level of dye removal. The isotherm study indicated the homogeneous distribution of active sites on the biomass surface, and the kinetic study suggested that chemisorption is the rate-limiting step which controlled the biosorption process. Based on the obtained results, Panus tigrinus biomass prepared can be used effectively to decolorize textile dyes and to tackle the pollution problems in the environment.